Investigation of a Model-Based Working Memory Training With and Without Distractor Inhibition and Its Comparative Efficacy: A Randomized Controlled Trial on Healthy Old Adults - Zuber, Priska; Geiter, Emanuel; de Quervain, Dominique J.-F.; Magon, Stefano (Frontiers in Aging Neuroscience, 2021)
Background: Various working memory (WM) trainings have been tested, but differences in experimental designs, lack of theoretical background and need of identifying task-related processes such as filtering efficiency limit conclusions about their comparative efficacy. Objectives: In this study we compared the efficacy of a model-based WM training with (MB+) and without (MB) distractor inhibition on improving WM capacity to a dual-n-back and active control condition. Methods: This randomized clinical trial included 123 healthy elderly adults (78 women, 45 men; aged 64.1±8.3 years). All groups underwent twelve 40-min training sessions over three weeks and four cognitive testing sessions. The first two sessions served as double-baseline to account for practice effects. Primary outcome was WM capacity post-training measured by complex span tasks. Near and far transfer was assessed by simple span, n-back, visuospatial and verbal learning, processing speed and reasoning tasks. Results: Due to preliminary termination (COVID-19) 93 subjects completed the post-training and 60 the follow-up session. On whole group level, practice-effects occurred from pre-baseline to baseline in WM capacity (b = 4.85, t(103) = 4.01, p < .001, r = 0.37). Linear mixed effects models revealed a difference in WM capacity post-training between MB+ and MB (b = -9.62, t(82) = -2.52), p = .014, r = 0.27) and a trend difference between MB+ and dual-n-back (b = -7.59, t(82) = -1.87), p = .065, r = 0.20) and control training (b = -7.08, t(82) = -1.86), p = .067, r = 0.20). Univariate analyses showed an increase between pre- and post-training for WM capacity within MB+ (t(22) = -3.34, p < 0.05) only. There was no difference between groups pre- and post-training regarding near and far transfer. Univariate analyses showed improved visuospatial learning within MB+ (t(21) = -3.8, p < .05), improved processing speed (t(23) = 2.19, p < .05) and n-back performance (t(23) = 2.12, p < .05) in MB and improved n-back performance (t(25) = 3.83, p < .001) in the dual-n-back training. Interpretation: A model-based WM training including filtering efficacy may be a promising approach to increase WM capacity and needs further investigation in randomized controlled studies.